Glass ceramic manufacturing method

By performing mask exposure on the matrix glass and two-stage crystallization heat treatment, microcrystalline glass with blackened and transparent parts is made, solving the problems of high strength and cost in the prior art, and achieving the effects of high transmittance and excellent mechanical properties.

CN119707294APending Publication Date: 2025-03-28CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924761.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to effectively manufacture microcrystalline glass with blackened parts and transparent parts, and its strength and cost are high.

Method used

By forming the matrix glass and using a mask exposure treatment and a crystallization heat treatment process, a microcrystalline glass with a blackened part and a transparent part is made. The process involves ultraviolet exposure on the matrix glass followed by two-stage crystallization heat treatment to form a microcrystalline glass with excellent mechanical properties.

Benefits of technology

The blackened part and transparent part of the microcrystalline glass are realized in the visible light band, and the microcrystalline glass and its products have excellent mechanical properties and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208970180000151
    Figure BDA0005208970180000151
  • Figure BDA0005208970180000201
    Figure BDA0005208970180000201
  • Figure BDA0005208970180000211
    Figure BDA0005208970180000211
Patent Text Reader

Abstract

The invention provides a method for manufacturing glass ceramics, which comprises the following steps of: forming matrix glass, and forming the matrix glass into the glass ceramics through a crystallization process, and the crystallization process comprises the steps of performing mask exposure treatment on the matrix glass and then performing crystallization heat treatment. The microcrystalline glass obtained by the method has a blackened part and a transparent part, the transparent part has high transmittance in a visible light wave band, and the blackened part has low transmittance in the visible light wave band. The obtained microcrystalline glass is suitable for chemical strengthening, and the microcrystalline glass and a microcrystalline glass product prepared from the microcrystalline glass have excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application for the invention patent application with application number 202410483551.1, application date April 22, 2024, and name “Microcrystalline glass, microcrystalline glass products and manufacturing methods thereof”. Technical Field

[0002] The invention relates to a method for manufacturing microcrystalline glass, in particular to a method for manufacturing microcrystalline glass having a blackened part and a transparent part. Background Art

[0003] In recent years, with the continuous rise and development of consumer electronic products, glass, as a transparent and high-performance material, has been widely used in electronic devices. Since electronic devices have many sophisticated electronic components inside, they need to be provided with a cover or a shell to protect the internal electronic components. With the diversification of market demand, the use scenarios of protective cover glass are becoming more and more complex, and its role is no longer just to protect the internal electronic components, but sometimes it also needs to have other functions. For example, in the vital signs monitoring of smart watches, the glass material needs to be partially transparent, but it needs to be shielded in other places to avoid the interference of stray light. Therefore, the glass material needs to have both black and transparent parts, which poses new challenges to the glass manufacturing process technology. In the prior art, the above-mentioned cover material can be manufactured by embedded design using two different materials, transparent and black, but due to the different strengths of the two materials, the large difference in expansion coefficients, and the need to process through holes, there are microcracks on the inner wall of the glass, which reduces the strength of the cover material, and it is difficult to process smaller holes or special-shaped graphics, and the production cost is high. Summary of the invention

[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a method for manufacturing microcrystalline glass having a blackened portion and a transparent portion, wherein the microcrystalline glass is suitable for chemical strengthening to form microcrystalline glass products.

[0005] The solution adopted by the present invention to solve the technical problem is:

[0006] (1) A method for manufacturing microcrystalline glass, the method comprising the following steps: forming a matrix glass, and subjecting the matrix glass to a crystallization process to form microcrystalline glass, wherein the crystallization process comprises subjecting the matrix glass to a mask exposure process and then to a crystallization heat treatment.

[0007] (2) The method for manufacturing a glass-ceramic according to (1), wherein the glass-ceramic comprises one or more blackened portions and one or more transparent portions, and the components of the glass-ceramic contain SiO 2 , R 2 O. Li 2 O、Al 2 O3 、ZrO 2 、CeO 2 and Ag 2 O, R 2 O is Na 2 O.K 2 One or both of O.

[0008] (3) According to the method for manufacturing microcrystalline glass described in (1) or (2), the mask exposure treatment includes ultraviolet exposure of a specific position or area of ​​the matrix glass, the ultraviolet light wavelength is preferably 313nm, and the exposure time is preferably 5 to 60 minutes.

[0009] (4) According to the method for manufacturing microcrystalline glass described in (1) to (3), the crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

[0010] (5) According to the method for manufacturing microcrystalline glass described in any one of (1) to (4), the average transmittance T of the transparent part of the microcrystalline glass with a thickness of 0.2 to 1.5 mm in the wavelength range of 400 to 800 nm is 400-800nm is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the 0.2-1.5 mm thick microcrystalline glass in the 400-800 nm wavelength range 400-800nm is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the 0.2 to 1.5 mm thick microcrystalline glass at 870 nm 870nm is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the 0.2 to 1.5 mm thick microcrystalline glass at 940 nm 940nm It is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.

[0011] (6) The method for producing glass-ceramics according to any one of (1) to (5), wherein the blackened portion of the glass-ceramics contains a crystalline phase, and the transparent portion of the glass-ceramics does not contain a crystalline phase.

[0012] (7) According to any one of the methods for manufacturing microcrystalline glass described in (1) to (6), the blackened portion of the microcrystalline glass contains a lithium metasilicate crystalline phase. In the blackened portion of the microcrystalline glass, the weight percentage of the lithium metasilicate crystalline phase is preferably 5 to 50%, more preferably 5 to 40%, and further preferably 10 to 30%.

[0013] (8) According to the method for manufacturing microcrystalline glass according to any one of (1) to (7), the components of the microcrystalline glass, expressed in weight percentage, include: SiO 2 : 65-78%, preferably SiO 2 : 68-77%, more preferably SiO 2 :69.5~75.5%; R 2 O: 2-12%, preferably R 2 O: 3-10%, more preferably R 2 O: 4-8%; Li 2 O: 5-15%, preferably Li 2 O: 7-13%, more preferably Li 2 O: 8.5-12%; Al 2 O 3 : 3-12%, preferably Al 2 O 3 : 4 to 10%, more preferably Al 2 O 3 :5~9%; ZrO 2 : 1.5-10%, preferably ZrO 2 : 2-8%, more preferably ZrO 2 :3~6.5%;CeO 2 : 0.01~0.6%, preferably CeO 2 : 0.07-0.4%, more preferably CeO 2 :0.08~0.3%;Ag 2 O: 0.01-0.8%, preferably Ag 2 O: 0.1-0.6%, more preferably Ag 2 O: 0.2~0.5%; Sb 2 O 3 : 0-1%, preferably Sb 2 O 3 : 0.01 to 0.7%, more preferably Sb 2 O 3 :0.07~0.5%; SnO2 : 0~0.5%, preferably SnO 2 : 0-0.3%, more preferably SnO 2 : 0 to 0.2%; MO: 0 to 5%, preferably MO: 0 to 3%, more preferably MO: 0 to 1%, and more preferably no MO; Ln 2 O 3 : 0-5%, preferably Ln 2 O 3 : 0-3%, more preferably Ln 2 O 3 : 0 to 1%, preferably no Ln 2 O 3 ;Fe 2 O 3 : 0~1%, preferably Fe 2 O 3 : 0-0.5%, more preferably Fe 2 O 3 : 0 to 0.2%, preferably no Fe 2 O 3 , the R 2 O is Na 2 O.K 2 O is one or two of them, MO is one or more of MgO, CaO, SrO, BaO, ZnO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0014] (9) According to the method for manufacturing glass-ceramics according to any one of (1) to (8), the components of the glass-ceramics, expressed in weight percentage, satisfy one or more of the following 14 conditions:

[0015] 1) SiO 2 / Li 2 O is 5.5 to 10.0, preferably SiO 2 / Li 2 O is 6.0 to 9.0, more preferably SiO 2 / Li 2 O is 7.0-8.5;

[0016] 2)(Sb 2 O 3 +SnO 2 ) / Ag 2 O is 0.1 to 5.0, preferably (Sb 2 O3 +SnO 2 ) / Ag 2 O is 0.5 to 3.5, more preferably (Sb 2 O 3 +SnO 2 ) / Ag 2 O is 1.0 to 2.6;

[0017] 3)(K 2 O+Na 2 O) / ZrO 2 is 0.5 to 7.1, preferably (K 2 O+Na 2 O) / ZrO 2 is 0.7 to 4.5, more preferably (K 2 O+Na 2 O) / ZrO 2 0.8~2.5;

[0018] 4) Ag 2 O / CeO 2 1.0~10.0, preferably Ag 2 O / CeO 2 1.5 to 6.5, more preferably Ag 2 O / CeO 2 2.0~4.5;

[0019] 5)Li 2 O / ZrO 2 1.0 to 7.5, preferably Li 2 O / ZrO 2 1.2 to 5.0, more preferably Li 2 O / ZrO 2 is 1.4 to 4.3, and Li 2 O / ZrO 2 1.6~3.0;

[0020] 6)(SiO 2 +Li 2 O) / ZrO 2 8.0 to 55.0, preferably (SiO 2 +Li 2 O) / ZrO 2 10.0 to 37.0, more preferably (SiO 2 +Li 2 O) / ZrO 2 12.0 to 25.0, more preferably (SiO 2 +Li 2 O) / ZrO 2 13.0~20.0;

[0021] 7) ZrO 2 / (Ag 2 O+CeO 2 ) is 2.3 to 50.0, preferably ZrO 2 / (Ag 2 O+CeO 2 ) is 6.5 to 35.0, and ZrO is more preferred 2 / (Ag 2 O+CeO 2 ) is 8.5 to 20.0, and ZrO is more preferred 2 / (Ag 2 O+CeO 2 ) is 11.0~18.0;

[0022] 8)(Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 1.0 to 30.0, preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 3.0 to 20.0, more preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 is 5.0 to 12.5, and more preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 7.5~10.0;

[0023] 9)(Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 0.1 to 10.0, preferably (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 0.4 to 5.0, more preferably (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2O is 0.7 to 3.7, and more preferably (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 1.5 to 3.2;

[0024] 10) SnO 2 / (CeO 2 +SnO 2 ) is 0 to 0.9, preferably SnO 2 / (CeO 2 +SnO 2 ) is 0 to 0.6, more preferably SnO 2 / (CeO 2 +SnO 2 ) is 0 to 0.5;

[0025] 11) R 2 O+Li 2 O+Al 2 O 3 15-30%, preferably R 2 O+Li 2 O+Al 2 O 3 17.5 to 29.5%, more preferably R 2 O+Li 2 O+Al 2 O 3 18.5 to 26%, more preferably R 2 O+Li 2 O+Al 2 O 3 20-25%;

[0026] 12)(SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 3.0 to 7.5, preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 3.7 to 6.5, and more preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2O) is 4.3 to 6.0, and more preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 4.8 to 5.8;

[0027] 13) MO / ZrO 2 2.5 or less, preferably MO / ZrO 2 1.5 or less, more preferably MO / ZrO 2 is less than 0.5;

[0028] 14) Sb 2 O 3 +SnO 2 : 0.05~1.2%, preferably Sb 2 O 3 +SnO 2 : 0.1 to 1%, more preferably Sb 2 O 3 +SnO 2 :0.2~0.7%,the R 2 O is Na 2 O.K 2 O, and MO is one or more of MgO, CaO, SrO, BaO, and ZnO.

[0029] (10) According to the method for producing glass-ceramics according to any one of (1) to (9), the refractive index n of the transparent portion of the glass-ceramics is d is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284; and / or Young's modulus E is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2, more preferably 492 to 532 kgf / mm 2 ; and / or the ball drop test height I is 200 mm or more, preferably 300 mm or more, more preferably 400 mm or more; and / or the dielectric loss tanδ is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 ; and / or dielectric constant ε r 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0; and / or linear expansion coefficient α 20℃-300℃ 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0030] (11) Microcrystalline glass, made by the method for making microcrystalline glass described in any one of (1) to (10).

[0031] (12) A glass-ceramic product, which is made from the glass-ceramic described in (11) through a chemical strengthening process.

[0032] (13) According to the microcrystalline glass product described in (12), the chemical strengthening process includes immersing the microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.

[0033] (14) A glass cover plate, which is made of the microcrystalline glass described in (11), or made of the microcrystalline glass products described in (12) to (13).

[0034] (15) A device comprising the microcrystalline glass described in (11), and / or the microcrystalline glass products described in (12) to (13), and / or the glass cover plate described in (14).

[0035] The beneficial effects of the present invention are as follows: the microcrystalline glass obtained by the method has a blackened part and a transparent part, the transparent part has a high transmittance in the visible light band, and the blackened part has a low transmittance in the visible light band. The microcrystalline glass obtained by the present invention is suitable for chemical strengthening, and the microcrystalline glass and microcrystalline glass products made thereof have excellent mechanical properties. DETAILED DESCRIPTION

[0036] Below, the embodiments of the present invention are described in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, about the repeated description part, although there is a situation of appropriate omission of description, the main purpose of the invention will not be limited thereby.

[0037] The glass-ceramics and glass-ceramics products of the present invention are materials having a crystalline phase (sometimes also referred to as crystal) and a glass phase, which are different from amorphous solids. The crystalline phase of the glass-ceramics and glass-ceramics products can be identified by the peak angles appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.

[0038] After repeated experiments and studies, the inventors of the present invention obtained the microcrystalline glass or microcrystalline glass products of the present invention by regulating the content and content ratio of specific components constituting microcrystalline glass and microcrystalline glass products to specific values ​​and precipitating specific crystalline phases.

[0039] In some embodiments, the glass-ceramics of the present invention comprises one or more blackened portions and one or more transparent portions, wherein the transparent portions refer to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the microcrystalline glass in the 400-800nm ​​band when the microcrystalline glass is processed into a thickness of 0.2-1.5mm. 400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the microcrystalline glass contains a crystalline phase, and the transparent portion of the microcrystalline glass does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass is uniformly distributed.

[0040] In some embodiments, the glass-ceramic product of the present invention comprises one or more blackened parts and one or more transparent parts, wherein the transparent part refers to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the microcrystalline glass product in the 400-800nm ​​band when the microcrystalline glass product is processed into a thickness of 0.2-1.5mm.400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the microcrystalline glass article contains a crystalline phase, and the transparent portion of the microcrystalline glass article does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass article is uniformly distributed.

[0041] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention are entirely blackened, and the blackened portion refers to the average transmittance (T 400-800nm ) is less than 5.0%. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass or microcrystalline glass article is uniformly distributed.

[0042] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention are entirely transparent, and the transparent portion refers to the average transmittance (T 400-800nm ) is more than 85.0%.

[0043] In some embodiments, the blackened portion in the glass-ceramics or glass-ceramics products of the present invention may form patterns of any shape and / or size.

[0044] Next, the scope of each component (ingredient) of the matrix glass, microcrystalline glass and microcrystalline glass products of the present invention is described. In this specification, unless otherwise specified, the content of each component is expressed in weight percentage (wt%) relative to the total amount of matrix glass, microcrystalline glass or microcrystalline glass product material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, composite salts and hydroxides used as raw materials for the matrix glass, microcrystalline glass or microcrystalline glass product components of the present invention decompose and transform into oxides when melted, the total amount of the oxide material is taken as 100%. In addition, in this specification, when it is only referred to as glass, it is the matrix glass before crystallization (i.e., crystallization process treatment), the matrix glass after crystallization (i.e., crystallization process treatment) is called microcrystalline glass, and microcrystalline glass products refer to products obtained after chemical strengthening of microcrystalline glass.

[0045] Unless otherwise indicated in specific cases, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoints, as well as all integers and fractions within the range, without limitation to the specific values ​​listed when the range is defined. The term "about" as used herein means that the formula, parameters and other quantities and features are not and need not be exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors and measurement errors, etc. "And / or" as used herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0046] In some embodiments of the present invention, the crystal phase (crystal) in the glass-ceramic or glass-ceramic product contains a lithium silicate crystal phase, preferably a lithium metasilicate crystal phase (Li 2 SiO 3 ) crystalline phase. In some embodiments, the lithium metasilicate crystalline phase has a higher weight percentage than the other crystalline phases. In some embodiments, the crystalline phase in the microcrystalline glass or microcrystalline glass article includes only the lithium metasilicate crystalline phase.

[0047] In some embodiments, in the blackened portion of the microcrystalline glass or microcrystalline glass products, the weight percentage of the lithium metasilicate crystalline phase is 5-50%, preferably the weight percentage of the lithium metasilicate crystalline phase is 5-40%, and more preferably the weight percentage of the lithium metasilicate crystalline phase is 10-30%. In some embodiments, in the blackened portion of the microcrystalline glass or microcrystalline glass products, the weight percentage of the lithium metasilicate crystalline phase is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%.

[0048] SiO 2 It is a glass-forming oxide and a skeleton for forming glass. It has a low dielectric constant and dielectric loss. SiO 2 It is a component of lithium metasilicate in glass-ceramics. 2 When the content is less than 65%, the hardness and expansion coefficient of the glass decrease, and the dielectric constant and dielectric loss of the glass increase. 2 When the content of SiO is higher than 78%, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products increases. 2The content range of SiO is 65-78%, preferably 68-77%, and more preferably 69.5-75.5%. In some embodiments, the SiO2 content may be about 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%. 2 .

[0049] Li 2 O is the main component of the crystals formed by the microcrystalline glass and microcrystalline glass products of the present invention. 2 When the content of O is less than 5%, the crystal content of the microcrystalline glass or microcrystalline glass products is reduced, and the transmittance of the blackened part is higher; when Li 2 When the O content is greater than 15%, the Young's modulus and drop ball test height of the glass decrease, the refractive index and dielectric loss of the glass increase, and the glass that is not exposed to UV light during the crystallization process of the matrix glass is prone to crystallization during the heat treatment process, and the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products decreases. 2 The content of O is limited to 5-15%, preferably 7-13%, and more preferably 8.5-12%. In some embodiments, about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% Li 2 O.

[0050] The inventors have found that, in some embodiments, the hardness of the glass and the height of the drop ball test increase with the SiO 2 / Li 2 O value increases, and the refractive index increases with SiO 2 / Li 2 O value increases and decreases. At the same time, when SiO 2 / Li 2 When SiO is lower than 5.5, the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products decreases, and the transmittance of the blackened part increases; when SiO 2 / Li 2 When SiO exceeds 10.0, the crystal content of the blackened portion of the microcrystalline glass and microcrystalline glass products is low, and the transmittance of the blackened portion is increased. 2 / Li 2 O is 5.5 to 10.0, more preferably SiO 2 / Li2 O is 6.0 to 9.0, and SiO is more preferred. 2 / Li 2 When SiO is 7.0 to 8.5, the transparent part of the glass-ceramic and glass-ceramic products has a high transmittance in the visible light band, while the blackened part has a low transmittance, which is particularly suitable for optical signal channels or light shielding systems of electronic products. 2 / Li 2 The value of O can be 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.

[0051] Alkali metal oxides R 2 O(R 2 O is Na 2 O.K 2 O) can promote the precipitation of lithium metasilicate crystals and improve the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products. 2 When the O content is less than 2%, the crystal content of the microcrystalline glass and microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved; when R 2 When the O content is greater than 12%, the Young's modulus and drop ball test height of the glass decrease, and the refractive index, dielectric constant and dielectric loss of the glass increase. 2 The content of O is limited to 2-12%, preferably 3-10%, and more preferably 4-8%. In some embodiments, about 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% of R 2 O.

[0052] Al 2 O 3 It can inhibit the decrease in the transmittance of the transparent part of microcrystalline glass and microcrystalline glass products after mask exposure and heat treatment, and improve the strength and hardness of the glass, and enhance the chemical stability of the glass. 2 O 3 When the content of Al is less than 3%, the hardness and Young's modulus of the glass decrease, and the linear expansion coefficient increases; 2 O 3When the content of Al is higher than 12%, the dielectric constant and dielectric loss of the glass increase, the crystal content of the blackened part of the microcrystalline glass and microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. 2 O 3 The content of Al is 3-12%, preferably 4-10%, and more preferably 5-9%. In some embodiments, the Al content may include about 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%. 2 O 3 .

[0053] In some embodiments, when R 2 O. Li 2 O and Al 2 O 3 Total content R 2 O+Li 2 O+Al 2 O 3 When it is less than 15%, the refractive index, hardness and Young's modulus of the glass decrease. 2 O+Li 2 O+Al 2 O 3 When it is greater than 30%, the dielectric constant and dielectric loss of the glass increase. 2 O+Li 2 O+Al 2 O 3 15 to 30%, more preferably R 2 O+Li 2 O+Al 2 O 3 17.5 to 29.5%, more preferably R 2 O+Li 2 O+Al 2 O 3 18.5-26%, more preferably R 2 O+Li 2 O+Al 2 O 3 In some embodiments, R 2 O+Li 2 O+Al 2 O 3About 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%.

[0054] The inventors have conducted a large number of experimental studies and found that in some embodiments, controlling SiO 2 and Al 2 O 3 Total content of SiO 2 +Al 2 O 3 With Li 2 O、Na 2 O.K 2 Total content of OLi 2 O+Na 2 O+K 2 The ratio of SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is in the range of 3.0 to 7.5, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products is lower, and the refractive index of the glass is lower, which can reduce the reflectivity of the light signal on the glass surface and increase the incidence rate of the light signal. Therefore, it is preferred that (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 3.0 to 7.5, and more preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 3.7 to 6.5, and more preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 O) is 4.3 to 6.0, and more preferably (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na2 O+K 2 In some embodiments, (SiO 2 +Al 2 O 3 ) / (Li 2 O+Na 2 O+K 2 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0, 10.1, 10.2, 10.3, 10.4, 10.5

[0055] ZrO 2 The accuracy of the black pattern formed by the blackened part of the glass after mask exposure can be adjusted, the interface distinction between the exposed part and the unexposed part can be improved, and the crystallization near the interface position of the unexposed part after heat treatment can be prevented, thereby maintaining the high transmittance of the unexposed part in the visible light band after heat treatment, and ensuring that the blackened part of the exposed part has a lower transmittance after heat treatment. 2 When the content of ZrO is less than 1.5%, the expansion coefficient of the glass increases. When the glass is heat treated, the unexposed part is easy to crystallize, resulting in a decrease in the transmittance of the transparent part. 2 When the content is higher than 10%, the crystal content of microcrystalline glass and microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. 2 The content of ZrO is 1.5-10%, preferably 2-8%, and more preferably 3-6.5%. In some embodiments, the ZrO may include about 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. 2 .

[0056] In some embodiments, controlling K 2 O、Na 2 Total content of O K 2 O+Na 2 O and ZrO 2 The ratio between the contents of 2 O+Na 2 O) / ZrO 2In the range of 0.5 to 7.1, the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products is high, the hardness and Young's modulus of the glass are high, and the dielectric constant of the glass is low. Therefore, it is preferred that (K 2 O+Na 2 O) / ZrO 2 is 0.5 to 7.1, more preferably (K 2 O+Na 2 O) / ZrO 2 is 0.7 to 4.5, and more preferably (K 2 O+Na 2 O) / ZrO 2 In some embodiments, (K 2 O+Na 2 O) / ZrO 2 The value of can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 6.0, 6.5, 7.0, 7.1.

[0057] In some embodiments, controlling Li 2 O content and ZrO 2 The ratio between the content of Li 2 O / ZrO 2 In the range of 1.0 to 7.5, the glass can have a lower refractive index and dielectric loss, and the accuracy of pattern formation in microcrystalline glass and microcrystalline glass products can be improved after the glass is exposed through a mask and heat treated. The transparent part of the microcrystalline glass and microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, Li 2 O / ZrO 2 1.0 to 7.5, more preferably Li 2 O / ZrO 2 is 1.2 to 5.0, and Li 2 O / ZrO 2 is 1.4 to 4.3, and Li is more preferred 2 O / ZrO 2 In some embodiments, Li 2 O / ZrO 2The value of can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5.

[0058] In some embodiments, controlling SiO 2 and Li 2 Total content of OSiO 2 +Li 2 O and ZrO 2 The ratio between the contents of SiO 2 +Li 2 O) / ZrO 2 In the range of 8.0 to 55.0, the hardness and drop ball test height of the glass can be improved, the expansion coefficient and dielectric constant of the glass can be reduced, the accuracy of the pattern formed in the microcrystalline glass and microcrystalline glass products after the glass is exposed through a mask and heat treated can be improved, and the drop ball test height of the microcrystalline glass and microcrystalline glass products can be improved; the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products is relatively low. Therefore, it is preferred that (SiO 2 +Li 2 O) / ZrO 2 8.0 to 55.0, more preferably (SiO 2 +Li 2 O) / ZrO 2 10.0 to 37.0, more preferably (SiO 2 +Li 2 O) / ZrO 2 12.0 to 25.0, more preferably (SiO 2 +Li 2 O) / ZrO 2 In some embodiments, (SiO 2 +Li 2 O) / ZrO 2The value of can be 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27. .0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0, 30.5, 31.0, 31.5, 32.0, 32.5, 33.0, 33.5, 34.0, 34.5, 35.0, 35.5, 36.0, 36.5, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0.

[0059] Alkaline earth metal oxide MO (MO is one or more of MgO, CaO, SrO, BaO, and ZnO) can improve the dielectric constant of glass, improve the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products. When the content of MO is higher than 5%, the dielectric constant and dielectric loss of the glass increase, and the Young's modulus and drop ball test height of the glass decrease. Therefore, the content of MO in the present invention is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and further preferably does not contain MO. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2% , 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% MO.

[0060] In some embodiments, when MO / ZrO 2 When the ratio is greater than 2.5, the dielectric loss of the glass increases, the hardness, Young's modulus and drop ball test height of the glass decrease, and the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products increases. 22.5 or less, more preferably MO / ZrO 2 is 1.5 or less, and more preferably MO / ZrO 2 In some embodiments, MO / ZrO 2 The value of can be 0, greater than 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5.

[0061] CeO 2 As a photosensitizer, it provides electrons for Ag, Sb, Sn and other components. 2 When the content is lower than 0.01%, it cannot provide enough electrons, resulting in too low crystal content of the microcrystalline glass, reducing the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products, and reducing the Young's modulus of the microcrystalline glass and microcrystalline glass products; when CeO 2 When the content is higher than 0.6%, the transmittance of the transparent part of the glass-ceramic and glass-ceramic products decreases, and the penetration depth of the glass-ceramic and glass-ceramic products in the ultraviolet band decreases, the crystal content inside the blackened part of the glass-ceramic and glass-ceramic products decreases, and the transmittance increases. 2 The content of is 0.01-0.6%, preferably 0.07-0.4%, and more preferably 0.08-0.3%. In some embodiments, it may contain about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6% CeO 2 .

[0062] Ag 2O acts as a crystal nucleating agent in the glass-ceramics and glass-ceramics products of the present invention, and plays a role in improving the blackening effect in the glass-ceramics and glass-ceramics products. 2 When the content of O is less than 0.01%, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products increases, and even cannot be blackened. In addition, the drop ball test height of the microcrystalline glass and microcrystalline glass products decreases, the expansion coefficient increases, and the graphic accuracy decreases. 2 When the content of O exceeds 0.8%, the transmittance of the transparent part decreases during the molding or heat treatment of the glass. Due to the excessively high content of crystal nuclei, the number of crystals in the microcrystalline glass and microcrystalline glass products increases, resulting in excessively fine grain size. The scattering effect of the blackened part of the crystal on visible light is weakened, which easily leads to an increase in the transmittance of the blackened part, and the glass is prone to crystallization during molding. Therefore, Ag 2 The content of O is limited to 0.01 to 0.8%, preferably 0.1 to 0.6%, and more preferably 0.2 to 0.5%. In some embodiments, the present invention may include about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%. %, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.8% Ag 2 O.

[0063] The inventors have found that, in some embodiments, controlling Ag 2 O content and CeO 2 The ratio of Ag content 2 O / CeO 2In the range of 1.0 to 10.0, the grain size of the blackened part of the microcrystalline glass and microcrystalline glass products is larger, the crystal content is higher, the light scattering effect in the visible light band is stronger, the transmittance of the blackened part is lower, and the hardness and drop ball test height of the microcrystalline glass and microcrystalline glass products increase. Therefore, Ag is preferred. 2 O / CeO 2 1.0 to 10.0, more preferably Ag 2 O / CeO 2 is 1.5 to 6.5, and Ag is more preferred 2 O / CeO 2 In some embodiments, Ag 2 O / CeO 2 The value of can be 1.0, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0064] In some embodiments, controlling ZrO 2 The content of Ag 2 O and CeO 2 Total content of Ag 2 O+CeO 2 The ratio between ZrO 2 / (Ag 2 O+CeO 2 ) in the range of 2.3 to 50.0, the expansion coefficient of the glass can be optimized, and the accuracy of the pattern formed in the microcrystalline glass after the glass is exposed through a mask and heat treated can be improved. At the same time, the transparent part of the microcrystalline glass and microcrystalline glass products has a higher transmittance, while the blackened part has a lower transmittance, and the hardness and ball drop height of the glass and microcrystalline glass products can be improved. Therefore, ZrO is preferred. 2 / (Ag 2 O+CeO 2 ) is 2.3 to 50.0, and ZrO is more preferred 2 / (Ag 2 O+CeO 2 ) is 6.5 to 35.0, and ZrO is more preferred 2 / (Ag 2 O+CeO 2 ) is 8.5 to 20.0, and ZrO is more preferred 2 / (Ag 2 O+CeO 2 ) is 11.0 to 18.0. In some embodiments, ZrO 2 / (Ag 2 O+CeO 2 ) can have a value of 2.3, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0.

[0065] Sb 2 O 3 and SnO 2 During UV exposure, Ce is absorbed 3+ The released electrons play the role of storing electrons and provide Ag for subsequent heat treatment. + Provide electrons to form Ag colloid nuclei and promote the blackening of microcrystalline glass. 2 O 3 +SnO 2 When the content of Sb is less than 0.05%, it is difficult for the microcrystalline glass or microcrystalline glass products to achieve the blackening effect. 2 O 3 +SnO 2 When the content of Sb is higher than 1.2%, the blackened part of the microcrystalline glass or microcrystalline glass products tends to have a higher transmittance. 2 O 3 +SnO 2 The content of Sb is 0.05 to 1.2%, preferably 0.1 to 1%, and more preferably 0.2 to 0.7%. 2 O 3 +SnO 2The content is about 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, and 1.2%.

[0066] SnO 2 It has a good effect of promoting the blackening of microcrystalline glass, but in some embodiments, when SnO 2 When the content of SnO is higher than 0.5%, the transmittance of the transparent part of the glass decreases or even becomes devitrified during molding or heat treatment. 2 The content of Sb is limited to 0 to 0.5%, preferably 0 to 0.3%, and more preferably 0 to 0.2%. 2 O 3 The content is limited to 0-1%, preferably 0.01-0.7%, and more preferably 0.07-0.5%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0. 24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5% SnO 2In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0. %, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% Sb 2 O 3 .

[0067] The inventors have found through a large number of experimental studies that in some embodiments, controlling Sb 2 O 3 and SnO 2 Total content of Sb 2 O 3 +SnO 2 With Ag 2 The ratio of O content (Sb 2 O 3 +SnO 2 ) / Ag 2 When O is in the range of 0.1 to 5.0, the dielectric loss of the glass can be reduced, the drop ball test height of the glass and the microcrystalline glass products can be increased, the transparent part of the microcrystalline glass and the microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, it is preferred that (Sb 2 O 3 +SnO 2 ) / Ag 2 O is 0.1 to 5.0, more preferably (Sb 2 O 3 +SnO 2 ) / Ag 2 O is 0.5 to 3.5, and more preferably (Sb 2 O 3 +SnO 2 ) / Ag 2 O is 1.0 to 2.6. In some embodiments, (Sb 2 O 3 +SnO2 ) / Ag 2 The value of O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0068] In some embodiments, controlling Ag 2 O、SnO 2 and Sb 2 O 3 Total content of Ag 2 O+SnO 2 +Sb 2 O 3 With CeO 2 The ratio between the content of Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 In the range of 1.0 to 30.0, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products can be lowered, and the hardness and Young's modulus can be increased while reducing the dielectric constant of the glass. 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 1.0 to 30.0, more preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 is 3.0 to 20.0, and more preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 is 5.0 to 12.5, and more preferably (Ag 2 O+SnO 2 +Sb 2 O 3 ) / CeO 2 In some embodiments, (Ag 2 O+SnO 2+Sb 2 O 3 ) / CeO 2 The value of can be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0 , 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.

[0069] In some embodiments, controlling Sb 2 O 3 SnO 2 、CeO 2 Total content of Sb 2 O 3 +SnO 2 +CeO 2 With Ag 2 The ratio of O content (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 When O is in the range of 0.1 to 10.0, the dielectric loss and expansion coefficient of the glass can be reduced, so that the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products is lower.

[0070] (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 0.1 to 10.0, more preferably (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 0.4 to 5.0, and more preferably (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 O is 0.7 to 3.7, and more preferably (Sb 2 O3 +SnO 2 +CeO 2 ) / Ag 2 O is 1.5 to 3.2. In some embodiments, (Sb 2 O 3 +SnO 2 +CeO 2 ) / Ag 2 The value of O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8. 8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0071] In some embodiments, when SnO 2 / (CeO 2 +SnO 2 ) is greater than 0.9, the transmittance of the transparent part of the glass decreases sharply during glass molding or heat treatment, and even completely loses transparency. 2 / (CeO 2 +SnO 2 ) is 0 to 0.9, more preferably SnO 2 / (CeO 2 +SnO 2 ) is 0 to 0.6, and SnO is more preferably 2 / (CeO 2 +SnO 2 ) is 0 to 0.5. In some embodiments, SnO 2 / (CeO 2 +SnO 2) can have a value of 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.07, 0.1, 0.13, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9.

[0072] Ln 2 O 3 (Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of) can adjust the dielectric constant and dielectric loss of the glass, and can be Ag + Provide electrons to promote the blackening of microcrystalline glass. 2 O 3 When Ln is higher than 5%, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products increases, and the dielectric constant and dielectric loss of the glass increase. 2 O 3 The content of Ln is limited to 0-5%, preferably 0-3%, more preferably 0-1%. In some embodiments, it is further preferred that Ln 2 O 3 In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 3.1%, 3.2%, 3. %, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% Ln 2 O 3 .

[0073] Fe 2 O 3 During the UV exposure of glass, it can absorb UV light and can be Ag+ Provide electrons to promote the blackening of glass-ceramics. 2 O 3 When the content of Fe is higher than 1%, the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products in the visible light band decreases, the transmittance of the blackened part increases, and the drop ball test height of the microcrystalline glass and microcrystalline glass products decreases. 2 O 3 The content of Fe is limited to 0-1%, preferably 0-0.5%, more preferably 0-0.2%. In some embodiments, it is further preferred that Fe is not contained. 2 O 3 In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, 0.83%, 0. %, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% of Fe 2 O 3 .

[0074] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the matrix glass, microcrystalline glass or microcrystalline glass product of the present invention; however, as raw materials and / or equipment for producing matrix glass, microcrystalline glass or microcrystalline glass products, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final matrix glass, microcrystalline glass or microcrystalline glass product, and this situation is also within the scope of protection of the patent of this invention.

[0075] The various performance indicators of the glass-ceramics and / or glass-ceramics products and / or matrix glass of the present invention are tested by the following methods:

[0076] <Light transmittance>

[0077] The light transmittance is tested according to the following method: the sample to be tested is processed into a certain thickness and the opposite surfaces are polished in parallel, and the test is carried out in accordance with the national standard "GB / T 7962.12-2010".

[0078] <Linear expansion coefficient>

[0079] Linear expansion coefficient (α 20℃-300℃ ) The data of 20°C-300°C are tested according to the national standard "GB / T7962.16-2010". In the present invention, the linear expansion coefficient is sometimes referred to as the expansion coefficient.

[0080] <Dielectric constant>

[0081] Dielectric constant (ε r ) The test was conducted in accordance with the national standard GB / T 7265.1-1987, and the data was tested at 1GHz.

[0082] <Dielectric loss>

[0083] The dielectric loss (tanδ) is tested according to the national standard GB / T 7265.1-1987, and the data is tested under 1GHz conditions.

[0084] <Drop ball test height>

[0085] A φ20×1mm sample is placed on a glass supporting fixture, and a 32g steel ball is dropped from a specified height. The maximum drop ball test height at which the sample can withstand the impact without breaking is the drop ball test height. Specifically, the test is implemented from a drop ball test height of 100mm. Without breaking, the height is changed in sequence through 100mm, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm, 900mm, 100mm, 1000mm, 1100mm, 1200mm and above. For the embodiment with "drop ball test height II", the microcrystalline glass product is the test object. The test data recorded as 1000mm in the embodiment indicates that the microcrystalline glass product withstands the impact without breaking even if a steel ball is dropped from a height of 1000mm. For the embodiment with "drop ball test height I", the matrix glass is the test object. The drop ball test height in the present invention is sometimes referred to as the drop ball height.

[0086] <Knoop hardness>

[0087] The load (N) when a diamond quadrangular pyramid indenter with an angle of 172.5° is pressed into a pyramid-shaped depression on the test surface is divided by the surface area (mm2) calculated by the length of the depression. 2) value. The test load was 100 (N) and the holding time was 15 (seconds). In the present invention, Knoop hardness may be simply referred to as hardness.

[0088] <Young's modulus>

[0089] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.

[0090]

[0091] G=V S 2 ρ

[0092] Where: E is Young's modulus, Pa;

[0093] G is the shear modulus, Pa;

[0094] V T is the shear wave velocity, m / s;

[0095] V S is the longitudinal wave velocity, m / s;

[0096] ρ is the glass density, g / cm 3 .

[0097] <Refractive Index>

[0098] Refractive index (n d ) Tested according to the method specified in GB / T7962.1-2010.

[0099] The matrix glass of the present invention has the following properties:

[0100] 1) In some embodiments, the refractive index (n d ) is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284.

[0101] 2) In some embodiments, the Young's modulus (E) of the matrix glass of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa.

[0102] 3) In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 .

[0103] 4) In some embodiments, the drop ball test height I of the matrix glass of the present invention is greater than 200 mm, preferably greater than 300 mm, and more preferably greater than 400 mm.

[0104] 5) In some embodiments, the dielectric loss (tan δ) of the matrix glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 .

[0105] 6) In some embodiments, the dielectric constant (ε r ) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0.

[0106] 7) In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0107] The microcrystalline glass of the present invention has the following properties:

[0108] 1) In some embodiments, the average transmittance (T 400-800nm) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0109] 2) In some embodiments, the average transmittance (T 400-800nm ) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0110] 3) In some embodiments, the transmittance (T 870nm ) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0111] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0112] In some embodiments, since the transparent portion of the glass-ceramics of the present invention does not produce crystals, it has the same properties as the above-mentioned matrix glass, such as Young's modulus (E), Knoop hardness (Hk 0.1 ), drop ball test height, dielectric loss (tanδ), dielectric constant (ε r ), linear expansion coefficient (α 20℃-300℃) etc. Specifically, in some embodiments, the Young's modulus (E) of the transparent part of the microcrystalline glass of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 In some embodiments, the drop ball test height of the transparent part of the microcrystalline glass of the present invention is 200 mm or more, preferably 300 mm or more, and more preferably 400 mm or more. In some embodiments, the dielectric loss (tan δ) of the transparent part of the microcrystalline glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 In some embodiments, the dielectric constant (ε r ) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0. In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

[0113] The microcrystalline glass product of the present invention has the following properties:

[0114] 1) In some embodiments, the average transmittance (T 400-800nm ) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0115] 2) In some embodiments, the average transmittance (T 400-800nm ) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0116] 3) In some embodiments, the transmittance (T 870nm ) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.

[0117] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.

[0118] 5) In some embodiments, the drop ball test height II of the microcrystalline glass product of the present invention is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.

[0119] In some embodiments, the matrix glass / microcrystalline glass / microcrystalline glass product of the present invention has a lower dielectric constant and dielectric loss, which can reduce the transmission loss of electrical signals.

[0120] In some embodiments, the matrix glass / glass-ceramics / glass-ceramics articles of the present invention have relatively high Knoop hardness, Young's modulus and ball drop height.

[0121] In some embodiments, the matrix glass / glass-ceramic / glass-ceramic product of the present invention has a lower linear expansion coefficient to improve the accuracy of the optical signal channel or mask pattern.

[0122] In some embodiments, the matrix glass / glass-ceramics / glass-ceramics products of the present invention have a relatively low refractive index, which can reduce the reflectivity of surface light signals and increase the incidence of light signals.

[0123] The microcrystalline glass, microcrystalline glass products, and matrix glass of the present invention can be widely made into glass cover plates or glass components due to the above-mentioned excellent properties; at the same time, the microcrystalline glass, microcrystalline glass products, matrix glass of the present invention, and glass cover plates or glass components made thereof can be used to manufacture various instruments or equipment, including but not limited to electronic equipment, medical equipment, decorations or handicrafts, such as mobile phones, watches, computers, biomedical detection, etc., for manufacturing local light shielding glass or patterned cover glass for mobile phones, smart phones, tablet computers, laptops, televisions, etc., or optical signal channel glass for smart watches, biomedical devices, etc., or for manufacturing patterned decorations or handicrafts glass.

[0124] The matrix glass, glass-ceramics and glass-ceramics products of the present invention can be produced and manufactured by the following methods:

[0125] The manufacturing method of the matrix glass comprises the following steps: weighing the raw materials according to the component ratio and mixing them uniformly, placing the uniformly mixed raw materials into a platinum or quartz crucible, melting, clarifying, homogenizing and then cooling at 1450-1600°C, pouring the molten glass liquid into a mold for forming, and introducing circulating cooling air to ensure that the glass does not crystallize, preferably preheating the mold to 200-500°C, placing the formed glass and the mold into an annealing furnace for heat preservation and annealing, and then turning off the power and cooling with the furnace to obtain the matrix glass.

[0126] The manufacturing method of microcrystalline glass includes the following steps: forming a matrix glass, treating the matrix glass through a crystallization process, or processing the matrix glass into a glass element of a specific shape and then treating it through a crystallization process to obtain the microcrystalline glass of the present invention. The method of processing a glass element of a specific shape of the present invention includes methods known to those skilled in the art such as hot pressing, grinding or polishing. The crystallization process treatment of the present invention includes mask exposure treatment of the matrix glass, and then crystallization heat treatment, and uniformly precipitating crystals at the glass exposure position. The mask exposure treatment of the present invention refers to ultraviolet exposure at a specific position or area of ​​the matrix glass, and the ultraviolet light wavelength is preferably 313nm. A special photomask pattern can be customized according to application requirements, and the exposure time is preferably 5 to 60 minutes. The crystallization heat treatment of the present invention can be carried out in one stage or in two stages, and preferably in two stages. The two-stage crystallization heat treatment refers to performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

[0127] The manufacturing method of the glass-ceramic product comprises the following steps: treating the glass-ceramic of the present invention by a chemical strengthening process, or processing the glass-ceramic into a glass-ceramic element of a specific shape and then treating it by a chemical strengthening process, to obtain the glass-ceramic product of the present invention. The method of processing into a specific shape of the present invention includes hot pressing, grinding or polishing, etc., which are known to those skilled in the art.

[0128] The chemical strengthening described in the present invention is an ion exchange method. During the ion exchange process, smaller metal ions in the glass-ceramics are replaced or "exchanged" by larger metal ions with the same valence state near the glass-ceramics. The replacement of smaller ions with larger ions builds up compressive stress in the glass-ceramics, forming a compressive stress layer.

[0129] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na + , K + , Rb + , Cs + Ion exchange is performed by immersing the glass-ceramic in a salt bath of at least one molten salt containing larger metal ions, which are used to replace smaller metal ions in the glass-ceramic. Alternatively, other monovalent metal ions such as Ag + 、Tl + , Cu +The one or more ion exchange processes used to chemically strengthen the glass-ceramic may include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions, with washing and / or annealing steps added between immersions.

[0130] In some embodiments, the glass-ceramics can be prepared by immersing in a molten Na salt (e.g., NaNO) at a temperature of about 350° C. to 470° C. 3 ), and / or K salts (such as KNO 3 ) and / or Na and K mixed salt bath for 1 to 36 hours to carry out ion exchange, preferably at a temperature range of 380°C to 460°C, and for a time range of 2 to 24 hours.

[0131] In some embodiments, the matrix glass of the present invention can be processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed into a glass-ceramic product by the above-mentioned crystallization process. In some embodiments, the matrix glass of the present invention can be processed into a glass element, and then the glass element is processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed into a glass-ceramic product by the above-mentioned crystallization process.

[0132] Example

[0133] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The present invention embodiments have been tried to ensure the accuracy of the values ​​(such as quantity, etc.), but some errors and deviations must be taken into account. The composition itself is given in weight % based on the oxide and has been standardized to 100%.

[0134] <Matrix Glass Example>

[0135] This embodiment adopts the above-mentioned method for manufacturing the matrix glass to obtain the matrix glass having the composition shown in Tables 1 to 4. In addition, the properties of each matrix glass are measured by the test method described in the present invention, and the measurement results are shown in Tables 1 to 4.

[0136] Table 1.

[0137]

[0138]

[0139] Table 2.

[0140]

[0141]

[0142] Table 3.

[0143]

[0144]

[0145] Table 4.

[0146]

[0147]

[0148] <Glass-ceramic Example>

[0149] This embodiment adopts the above-mentioned method for manufacturing microcrystalline glass to obtain microcrystalline glass having the composition shown in Tables 5 to 8. In addition, the characteristics of each microcrystalline glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 5 to 8. The transmittance of the microcrystalline glass in the following embodiments is tested using a 1 mm thick sample.

[0150] Table 5.

[0151]

[0152]

[0153] Table 6.

[0154]

[0155]

[0156] Table 7.

[0157]

[0158]

[0159] Table 8.

[0160]

[0161]

[0162] <Glass-ceramic product example>

[0163] This embodiment adopts the manufacturing method of the above-mentioned microcrystalline glass products to obtain microcrystalline glass products having the compositions shown in Tables 9 to 12. In addition, the characteristics of each microcrystalline glass product are measured by the testing method described in the present invention, and the measurement results are shown in Tables 9 to 12. The transmittance of the microcrystalline glass products in the following embodiments is tested using a 1 mm thick sample.

[0164] Table 9.

[0165]

[0166]

[0167] Table 10.

[0168]

[0169]

[0170] Table 11.

[0171]

[0172]

[0173] Table 12.

[0174]

[0175]

Claims

1. A method for manufacturing glass-ceramics, characterized in that: The method comprises the following steps: forming a matrix glass, and subjecting the matrix glass to a crystallization process to form a microcrystalline glass, wherein the crystallization process comprises performing a mask exposure process on the matrix glass, and then performing a crystallization heat treatment.

2. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The microcrystalline glass comprises one or more blackened parts and one or more transparent parts, and the components of the microcrystalline glass include SiO2, R2O, Li2O, Al2O3, ZrO2, CeO2 and Ag2O, and the R2O is one or two of Na2O and K2O.

3. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The mask exposure process includes ultraviolet exposure of a specific position or area of ​​the substrate glass, the wavelength of the ultraviolet light is preferably 313 nm, and the exposure time is preferably 5 to 60 minutes.

4. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes a nucleation process at a first temperature, and then a crystal growth process at a second temperature higher than the nucleation process temperature. The first temperature is preferably 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. The second temperature is preferably 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.

5. The method for manufacturing glass-ceramics according to claim 1, characterized in that: Average transmittance T of the transparent part of 0.2-1.5mm thick glass-ceramics in the 400-800nm ​​band 400-800nm is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the 0.2-1.5 mm thick microcrystalline glass in the 400-800 nm wavelength range 400-800nm is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the 0.2 to 1.5 mm thick microcrystalline glass at 870 nm 870nm is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the 0.2 to 1.5 mm thick microcrystalline glass at 940 nm 940nm It is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.

6. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The blackened portion of the microcrystalline glass contains a crystalline phase, and the transparent portion of the microcrystalline glass does not contain a crystalline phase.

7. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The blackened portion of the microcrystalline glass contains a lithium metasilicate crystalline phase. In the blackened portion of the microcrystalline glass, the weight percentage of the lithium metasilicate crystalline phase is preferably 5 to 50%, more preferably 5 to 40%, and further preferably 10 to 30%.

8. The method for producing glass-ceramics according to any one of claims 1 to 7, characterized in that: The components of the microcrystalline glass are expressed by weight percentage, comprising: SiO2: 65-78%, preferably SiO2: 68-77%, more preferably SiO2: 69.5-75.5%; R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; Al2O3: 3-12%, preferably Al2O3 : 4-10%, preferably Al2O3: 5-9%; ZrO2: 1.5-10%, preferably ZrO2: 2-8%, more preferably ZrO2: 3-6.5%; CeO2: 0.01-0.6%, preferably CeO2: 0.07-0.4%, more preferably CeO2: 0.08-0.3%; Ag2O: 0.01-0.8%, preferably Ag2O: 0.1-0.6%, more preferably Ag2O: 0.2-0.5%; Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%; MO: 0-5%, preferably MO: 0-3%, more preferably MO: 0-1%, more preferably no MO; Ln2O3: 0-5%, preferably Ln2O3: 0-3%, more preferably Ln2 O3: 0-1%, and it is further preferred that Ln2O3 is not contained; Fe2O3: 0-1%, preferably Fe2O3: 0-0.5%, more preferably Fe2O3: 0-0.2%, and it is further preferred that Fe2O3 is not contained, the R2O is one or two of Na2O and K2O, MO is one or more of MgO, CaO, SrO, BaO, and ZnO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

9. The method for producing glass-ceramics according to any one of claims 1 to 8, characterized in that: The components of the glass-ceramics are expressed in weight percentage and meet one or more of the following 14 conditions: 1) SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, and more preferably SiO2 / Li2O is 7.0 to 8.5; 2) (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; 3) (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; 4) Ag2O / CeO2 is 1.0 to 10.0, preferably Ag2O / CeO2 is 1.5 to 6.5, and more preferably Ag2O / CeO2 is 2.0 to 4.5; 5) Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0; 6) (SiO2 + Li2O) / ZrO2 is 8.0 to 55.0, preferably (SiO2 + Li2O) / ZrO2 is 10.0 to 37.0, more preferably (SiO2 + Li2O) / ZrO2 is 12.0 to 25.0, and further preferably (SiO2 + Li2O) / ZrO2 is 13.0 to 20.0; 7) ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0; 8) (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 20.0, more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0 to 12.5, and further preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0; 9) (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2; 10) SnO2 / (CeO2+SnO2) is 0 to 0.9, preferably SnO2 / (CeO2+SnO2) is 0 to 0.6, and more preferably SnO2 / (CeO2+SnO2) is 0 to 0.5; 11) R2O+Li2O+Al2O3 is 15-30%, preferably R2O+Li2O+Al2O3 is 17.5-29.5%, more preferably R2O+Li2O+Al2O3 is 18.5-26%, and further preferably R2O+Li2O+Al2O3 is 20-25%; 12) (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and further preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8; 13) MO / ZrO2 is 2.5 or less, preferably MO / ZrO2 is 1.5 or less, and more preferably MO / ZrO2 is 0.5 or less; 14) Sb2O3+SnO2: 0.05-1.2%, preferably Sb2O3+SnO2: 0.1-1%, more preferably Sb2O3+SnO2: 0.2-0.7%, wherein R2O is one or two of Na2O and K2O, and MO is one or more of MgO, CaO, SrO, BaO and ZnO.

10. The method for manufacturing glass-ceramics according to claim 1, characterized in that: The refractive index n of the transparent part of the microcrystalline glass d is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284; and / or Young's modulus E is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa; and / or Knoop hardness Hk 0.1 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 ; and / or the ball drop test height I is 200 mm or more, preferably 300 mm or more, more preferably 400 mm or more; and / or the dielectric loss tanδ is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 ; and / or dielectric constant ε r 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and even more preferably 6.3 to 7.0; and / or linear expansion coefficient α 20℃-300℃ 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.

11. Glass-ceramics, characterized in that: The microcrystalline glass is manufactured by the manufacturing method of any one of claims 1 to 10.

12. A glass-ceramic product, characterized in that: The microcrystalline glass according to claim 11 is made by a chemical strengthening process.

13. The glass-ceramic product according to claim 12, characterized in that: The chemical strengthening process includes immersing the microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.

14. A glass cover plate, characterized in that: It is made of the microcrystalline glass described in claim 11, or made of the microcrystalline glass products described in claims 12 to 13.

15. A device, characterized in that Contains the microcrystalline glass according to claim 11, and / or contains the microcrystalline glass product according to claims 12 to 13, and / or contains the glass cover plate according to claim 14.